Polyamide-metal laminates

By forming a connecting layer containing carboxylic acid groups and amino-silane on the metal surface, the problem of insufficient binding strength and hydrolysis resistance of polyamide and metal in high-temperature aqueous glycol solution in the prior art is solved, and high Properties of polyamide-metal laminates.

CN114829125BActive Publication Date: 2024-12-13DUPONT POLYMERS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080082151.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-26
Filing Date
2020-11-25
Publication Date
2024-12-13
Estimated Expiration
2040-11-25

AI Technical Summary

Technical Problem

The prior art is difficult to produce sufficiently light and high temperature-resistant metal parts in the area under the hood of the automobile, especially in the environment in high-temperature aqueous glycol solutions, and the direct adhesion of polyamide to metals is difficult to meet the high performance needs.

Method used

Using a connecting layer of a polymer containing a carboxylic acid group and an amino-silane, a cyclic imide structure is formed through chemical reactions, which enhances the bonding strength of the polyamide and metal, and maintains hydrolysis resistance under high temperature conditions.

Benefits of technology

The high bonding strength and hydrolysis resistance of the polyamide-metal laminate under long-term exposure in high-temperature aqueous glycol solution exceed the performance of traditional surface treatment methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114829125B_ABST
    Figure CN114829125B_ABST
Patent Text Reader

Abstract

Novel polyamide-metal laminates with desirable hydrolysis resistance are provided. These laminates comprise (A) a metal, (B) a tie layer and (C) a polyamide composition. The tie layer is formed from a composition comprising (B1) a polymer containing a comonomer having at least two adjacent carboxylic acid groups and (B2) an amino-silane containing a primary amine group and at least one hydroxyl group.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority under 35 USC §365 to U.S. Provisional Application No. 62 / 940,397, filed on November 26, 2019, which is incorporated herein by reference in its entirety. Background Art

[0003] Several patents and publications are cited in this specification in order to more fully describe the state of the art to which the present invention relates. The entire disclosure of each of these patents and publications is incorporated herein by reference.

[0004] Novel polyamide-metal laminates are described herein that have desirable hydrolysis resistance and include novel tie layers for attaching polyamide compositions to metal surfaces. Also described herein are compositions suitable for forming tie layers on metals, metal parts having tie layers, articles including the polyamide-metal laminates, and methods for making these polyamide-metal laminates.

[0005] Polyamide-based compositions typically have desirable chemical resistance, processability and heat resistance properties. This makes them particularly well suited for demanding high-performance automotive and electrical / electronic applications, such as vehicle radiator and heater hoses. In the automotive field, there is currently a general desire to continuously reduce the weight of the various components that make up an automobile.

[0006] U.S. Patent Application Publication No. 2003 / 0116269 discloses a water-based primer composition comprising an organosilane for use on a metal surface to mainly combine two metals with each other. U.S. Patent Application Publication No. 2003 / 0180552 discloses a method for treating a metal surface with a silane composition to improve the adhesion of a polymer to a metal surface. U.S. Patent Application Publication No. 2007 / 0056469 discloses a method for treating a metal surface with a silane composition to improve the adhesion of a polymer to a metal surface. The silane composition includes a silane coating composition containing at least one water-soluble or dispersible silane and a polymer resin. The polymer resin is water-insoluble and is used as an aqueous dispersion.

[0007] However, there remains a need for even lighter weight articles for making components for under-the-hood applications in vehicles, and these articles include fewer parts and are easier to manufacture than currently available automotive parts. Direct bonding of aluminum or other lightweight metals to polyamides would eliminate parts and provide lower weight articles. However, such direct bonding must be able to withstand the high temperatures found in the under-the-hood area of ​​an automobile, especially when the article is exposed to high temperature aqueous glycol solutions. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 Schematic diagram showing the expected chemical structure of the metal (A), tie layer (B), and polyamide (C) of a laminated polyamide-aluminum.

[0009] Figure 2 Schematic diagram showing the expected chemical structure after forming a tie layer (B) on aluminum (A).

[0010] Figure 3 Schematic diagram showing another expected chemical structure after forming a tie layer (B) on aluminum (A).

[0011] Figure 4 Schematic diagram showing the expected chemical structure when no aminosilane (B2) is included in the tie layer (B) (comparison)

[0012] Figure 5 Schematic diagram showing the expected chemical structure when the carboxylic acid-containing polymer (B1) is not included in the tie layer (B) (Comparison)

[0013] Figure 6 A cross-sectional side view of a polyamide cap test sample is shown.

[0014] Figure 7 Shown is a cross-sectional side view of a polyamide cap test sample in a lamination apparatus for lamination with a metal layer via a tie layer to form a polyamide-metal laminate with a tie layer.

[0015] Figure 8 Shown is a cross-sectional side view of a polyamide-metal laminate with a tie layer in an apparatus for determining the bond strength between a polyamide cap test specimen and a metal layer.

[0016] Fig. 9 Shown is a perspective view of a test sample for determining bond strength according to ISO-19095-3. DETAILED DESCRIPTION

[0017] abbreviation

[0018] The claims and description herein are construed using the abbreviations and definitions listed below.

[0019] "h" and "hrs" mean hours.

[0020] "%" means the term percentage.

[0021] "Mole %" means mole percent.

[0022] "wt%" means percent by weight.

[0023] "Parts" means parts by weight.

[0024] "g" means grams

[0025] definition

[0026] As used herein, the article "a" refers to one as well as more than one and does not necessarily limit its referent noun to the grammatical category of the singular.

[0027] As used herein, the term "article" refers to an article, thing, structure, object, element, device, etc., in a form, shape, configuration suitable for a particular use / purpose without further processing of the entire entity or a portion thereof. An article may include one or more elements or subassemblies that are partially completed and await further processing or assembly with other elements / subassemblies that will together constitute the completed article. In addition, as used herein, the term "article" may refer to a system or configuration of articles.

[0028] As used herein, the term "solution" refers to an aqueous mixture of ingredients wherein the ingredients are dissolved, suspended or dispersed in water, alcohol, another suitable liquid, or a combination of two or more suitable liquids.

[0029] As used herein, the term "pure aluminum" refers to aluminum metal comprising at least 99 weight percent aluminum based on the total weight of the pure aluminum.

[0030] As used herein, the term "aluminum alloy" refers to aluminum metal containing less than 99 weight percent aluminum based on the total weight of the alloy and containing one or more other metals and optionally one or more non-metal elements.

[0031] As used herein, the term "tie layer" refers to a composition that bonds the metal to the polyamide composition without mechanical bonding, although additional bonding by mechanical means is optional if desired. The tie layer forms a sandwich structure, wherein the tie layer is the middle layer, the metal is an outer layer or outer layer directly attached to the tie layer, and the polyamide composition forms another outer layer directly attached to the tie layer. In other words, the metal layer is directly attached to one face of the tie layer, and the polyamide composition is directly attached to the opposite face of the tie layer.

[0032] Range and preferred variants

[0033] Unless expressly stated otherwise, any ranges set forth herein expressly include their endpoints. Listing an amount, concentration, or other value or parameter as a range specifically discloses all possible ranges formed by any possible upper range limit and any possible lower range limit, regardless of whether such pairs of upper and lower range limits are expressly disclosed herein. The compounds, methods, and articles described herein are not limited to the specific values ​​disclosed when defining a range in the specification.

[0034] The disclosure herein of any variation of the methods, compounds, and articles described herein with respect to materials, chemical entities, methods, steps, values, and / or ranges, etc., whether or not identified as preferred, is specifically intended to include any possible combination of that variation with any other materials, methods, steps, values, ranges, etc. described herein. Any combination of features disclosed is a preferred variation of the methods, compounds, and articles described herein.

[0035] Overview

[0036] Polyamide-metal laminates are described herein that include a polyamide composition bonded to a metal using a tie layer having a specific composition. Preferably, the polyamide-metal laminate exhibits a desired hydrolysis resistance when exposed to an ethylene glycol / water solution at 130° C. for 1000 hours compared to the initial bond strength prior to exposure to the ethylene glycol / water solution.

[0037] Also described herein are tie layers for improving the bonding of metals to polyamide compositions and methods for making these tie layers.

[0038] Also preferably, the polyamide-metal laminate comprises (A) a metal, (B) a tie layer formed on a surface of the metal, and (C) a polyamide formed on a surface of the tie layer, wherein the tie layer comprises:

[0039] B1) a polymer comprising carboxylic acid groups; and

[0040] B2) amino-silanes containing a primary amine group and at least one hydroxyl group;

[0041] At least two carboxylic acid groups in polymer (B1) are adjacent to each other, and the molar ratio of two adjacent carboxylic acid groups in (B1) to primary amine groups in (B2) is from 1:0.8 to 1:14.

[0042] Also described herein are compositions comprising (B1) and (B2) as described above, metal parts having a tie layer (B), methods for preparing polyamide metal laminates, and articles comprising the polyamide metal laminates.

[0043] Polyamide-metal laminates

[0044] The polyamide-metal laminates as disclosed herein can be used to prepare articles of any shape, such as a polyamide hose (polyamide (C)) bonded to a metal heat sink (metal (A)) using a tie layer (B). The tie layer (B) disclosed herein can be applied or coated on the metal (A) to provide a tie / metal laminate. These tie / metal laminates can then be bonded to a polyamide composition to prepare a polyamide-metal laminate.

[0045] Metal layer (A)

[0046] Metal (A) can be any metal that can form a bond with the hydroxyl group of aminosilane (B2). The example of metal (A) includes carbon steel, galvanized steel, stainless steel, steel castings, aluminum, titanium and alloys thereof. Metal (A) is preferably a light metal, such as aluminum or titanium, preferably aluminum. The metal can be a pure metal or a metal alloy. The metal alloy can include a mixture of metals. Alternatively, one or more metals can be combined with one or more non-metallic elements such as carbon or silicon to form an alloy. When the metal is aluminum, the aluminum content of the aluminum alloy should be at least about 70% by weight aluminum, preferably at least about 80% by weight aluminum, and more preferably at least 90% by weight aluminum.

[0047] Metal surface cleaning

[0048] Before forming the connecting layer (B) on the metal (A), cleaning of the metal surface may or may not be necessary. When the metal surface cleaning is required, methods typically used in the art for removing contaminants and oxides from the metal surface can be used. Metal surface cleaning includes chemical treatment and mechanical methods, as well as a combination of two or more suitable cleaning methods. Examples of such cleaning methods include, but are not limited to, polishing; polishing with abrasives such as sandpaper; atmospheric plasma treatment, corona discharge treatment; sandblasting; washing with a detergent solution, a detergent solution, a solvent or deionized water; and chemical etching. When polishing the metal, a solution containing an abrasive can be used. Non-limiting examples of abrasives include calcium carbonate, sodium bicarbonate, calcium sulfate, magnesium sulfate and combinations thereof. The solution may also contain alcohols, such as ethanol, methanol and isopropanol. The detergent solution preferably contains a cationic, anionic or nonionic surfactant, or a combination of two or more surfactants. The detergent solution may be any detergent or surfactant solution capable of removing contaminants on the metal surface. Examples of suitable detergent solutions are well known in the art.

[0049] When the metal is aluminum or an aluminum alloy, the aluminum should be cleaned to react with aminosilane (B2). Any cleaning method can be used. A preferred method for cleaning aluminum or an aluminum alloy is to polish the surface of the aluminum or aluminum alloy by an abrasive such as sandpaper in water or by sandblasting. Without being bound by theory, it is believed that the surface of the aluminum needs to be cleaned and optionally activated to obtain sufficient hydrolysis resistance to form a polyamide-metal laminate. An example of analyzing the aluminum surface is X-ray photoelectron spectroscopy (XPS). Typically, the surface of the aluminum or aluminum alloy is oxidized or contaminated with oil, so in addition to the signal of aluminum, signals of carbon and oxygen atoms are observed. In order to obtain sufficient hydrolysis resistance to form a polyamide-metal laminate, the aluminum signal analyzed by XPS should be 15% or more, preferably 20% or more. The percentage of the aluminum signal is based on the total molar number of elements present on the aluminum surface. Alternatively, the percentage is based on the "atomic %" of the total number of atoms detected in the analysis after applying the relative sensitivity factor and appropriately integrating the peak area of ​​the XPS spectrum. Another example of analyzing aluminum surfaces is time-of-flight secondary ion mass spectrometry (TOF-SIMS). Again, without being bound by theory, it is believed that one or more hydroxyl groups must be present on the aluminum surface to obtain sufficient hydrolysis resistance for the polyamide-metal laminate. The number of hydroxyl groups is analyzed by TOF-SIMS as aluminum hydroxide signals (Al(OH)3 or AlO(OH)·nH2O).

[0050] Connection layer (B)

[0051] The tie layer (B) that can be used to prepare the polyamide-metal laminate described herein comprises a polymer (B1) and an amino-silane (B2). The polymer (B1) comprises a carboxylic acid group. The amino-silane (B2) comprises a primary amine group and at least one hydroxyl group in the amino-silane molecule. The tie layer (B) can be a mixture of a polymer (B1) and an amino-silane (B2), or a reaction product of a polymer (B1) and an amino-silane (B2). When the tie layer (B) is a reaction product, the carboxylic acid group of the polymer (B1) reacts with the amino group of the amino-silane (B2). In some preferred tie layers, this reaction forms a cyclic imide, in which the silane group is attached to the imide nitrogen. It is believed that the reaction between the carboxylic acid group of the polymer (B1) and the amino group of the amino-silane (B2) will occur after being heated to a temperature of, for example, 220 degrees Celsius or higher.

[0052] Polymer (B1)

[0053] The polymer (B1) for preparing the connecting layer (B) comprises a carboxylic acid group. The carboxylic acid group can be a derivative of a carboxylic acid group, such as but not limited to a carboxylate, an alkyl ester (including a monoester and a diester) or a carboxylic anhydride. At least two carboxylic acid groups in (B1) must be adjacent to each other. Preferably, adjacent carboxylic acid groups are derived from an anhydride group, such as a copolymerization unit of maleic anhydride, because the anhydride group provides two adjacent carboxylic acid groups when hydrolyzed. As described below, adjacent carboxylic acid groups contribute to forming a cyclic imide structure with the nitrogen atom of the amino group.

[0054] Typically, polymer (B1) can be prepared by copolymerization of one or more monomers (B1-a) having ethylenically unsaturated groups with one or more monomers (B1-b) having ethylenically unsaturated groups and at least two adjacent carboxylic acid groups or derivatives thereof. As used herein, the term "adjacent carboxylic acid groups" refers to a molecule in which at least two carbon atoms are directly bonded to each other by a single bond or a double bond and each of the at least two carbon atoms is substituted by a carboxylic acid group. Monomer (B1-a) may also have a carboxylic acid group. Monomers (B1-a) having ethylenically unsaturated groups include, but are not limited to, unsaturated aliphatic hydrocarbons such as ethylene, propylene, butene, octene and isopropylene; aromatic monomers such as styrene and 4-methylstyrene; acrylic acid; methacrylic acid; acrylates such as acrylates or esters; methacrylates such as methacrylates or esters; and combinations of two or more of these. Preferred monomers (B1-b) having dicarboxylic acid groups or derivatives thereof include, but are not limited to, maleic acid, fumaric acid, itaconic acid, citraconic acid and derivatives of these acids such as anhydrides, salts, diesters and monoesters. Preferred are maleic anhydride and alkyl monoesters of maleic acid. In the copolymer of monomer (B1-a) and monomer (B1-b), based on the total number of copolymerization moles of (B1-a) and (B1-b), the preferred molar content of the residue of monomer (B1-b) is 10 mol % or more, more preferably 20 mol % or more, further more preferably 40 mol % or more. Based on the total weight percentage of polymer (B1), the content of two adjacent carboxylic acid groups in polymer (B1) can be 2 wt % or more, preferably 5 wt % or more. The remainder of the copolymerization unit of polymer B1 can be composed of or substantially composed of up to 90 mol % or more preferably up to 80 mol % or more of (B1-a).

[0055] The polymer (B1) can be prepared by direct polymerization from monomers having a dicarboxylic acid group or a derivative thereof (B1-b) such as maleic acid, fumaric acid and derivatives thereof.

[0056] Polymer (B1) can also be prepared by grafting maleic anhydride to the backbone of polymer (B1) and hydrolyzing the anhydride to form two carboxylic acid groups.

[0057] Examples of suitable polymers (B1) include, for example, poly(butadiene-maleic acid) copolymers, propylene-maleic acid copolymers, ethylene-maleic acid copolymers, ethylene-maleic anhydride copolymers, propylene-maleic anhydride copolymers, poly-maleic acid, poly(isobutylene-maleic acid) or their hydrolysates, ethylene-maleic anhydride copolymers or those hydrolysates, and combinations of two or more of these polymers.

[0058] Examples of suitable polymers (B1) in which carboxylic acid groups are grafted onto the backbone of the polymer (B1) include, for example, maleic anhydride grafted ethylene octene copolymers, maleic anhydride grafted ethylene butene copolymers, maleic anhydride grafted ethylene propylene copolymers and combinations of two or more of these polymers.

[0059] Commercially available copolymers that can be used as polymer (B1) in the present invention include ZeMac® available from Vertellus TM E60, E400 and Solution S67025 and ISOBAM available from Kuraray Co., Ltd. TM 104.

[0060] Amino-silane (B2)

[0061] The amino-silane (B2) contains a primary amine group and at least one hydroxyl group in the amino-silane molecule. The amino-silane (B2) used for the connecting layer (B) is represented by formula (I):

[0062]

[0063] In formula (I), R 1 , R 2 and R 3 R is independently selected from H, a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms. 4 It is H; R 5 independently selected from H and -(CH2) y -NH2; and x and y are independently selected from integers from 1 to 6, inclusive. 1 , R 2 and R 3 At least one of is H. Preferably, R 1 , R 2 , R 3 , R 4 and R 5 is H and is represented by formula (II).

[0064]

[0065] In formula (II), x is in the range of from 1 to 6.

[0066] Non-limiting examples of suitable amino-silanes (B2) include 3-aminopropyltrimethoxysilane, 2-aminoethyltrimethoxysilane, 3-aminopropyltriethoxysilane, 2-aminoethyltriethoxysilane and N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, and combinations of two or more of these aminosilanes.

[0067] Aminosilane can be hydrolyzed in water and become an oligomer. Such an oligomer can be used in the present invention.

[0068] Composition

[0069] As mentioned above, tie layer (B) can be the reaction product of polymer (B1) and amino-silane (B2), or the unreacted mixture of these materials.In the preparation process of tie layer (B), use the composition comprising the following: (B1) comprises the polymer of carboxylic acid group and (B2) comprises the amino-silane of primary amine group and at least one hydroxyl.Suitable polymer (B1) and amino-silane (B2) are described in detail above.The carboxylic acid group of polymer (B1) can exist in the form of salt, for example as ammonium salt or alkali metal salt.Composition can further comprise solvent, such as but not limited to water or alcohol / water mixture to form solvent mixture.Composition can be an emulsion or dispersion comprising amino-silane material and polymer, or composition can be a solution.

[0070] The total concentration of the combination of at least one amino-silane (B2) and at least one polymer (B1) in the composition may be in the range of from about 0.5 to 20 wt. %, preferably from 1 to 15 wt. %, and more preferably from 1 to 10 wt. % of the total concentration of polymer (B1) and aminosilane (B2), based on the total weight of the composition.

[0071] The composition may further include a pH regulator. Examples of pH regulators include, for example, ammonia, sodium hydroxide, potassium hydroxide, sodium carbonate and 1,8-diazabicyclo[5.4.0]undec-7-ene, salts of these materials, and mixtures of these materials and their salts. When the composition is a solution, the pH of the solution is preferably from 5 to 14, more preferably from 7 to 12, and further preferably from 8 to 11. Without being bound by theory, it is believed that the carboxylic acid groups of polymer (B1) are electrolytically dissociated in alkaline solutions; therefore, polymer (B1) is stable in alkaline solutions. At the same time, the amino groups of aminosilane (B2) are ionized in alkaline solutions. It is believed that these two groups interact with each other in alkaline solutions; therefore, when the solution is alkaline, the solution is stable. When the solution is in a weak acid range (pH of 5-7), the carboxylic acid group portion of polymer (B1) is electrolytically dissociated; therefore, due to the same reasons disclosed above, the solution is also stable.

[0072] Tie layer B may further comprise one or more additional components. Suitable additional components include, but are not limited to, reinforcing agents, such as carbon black or glass fibers, as described below with respect to polyamide composition C; other polymers, such as polyacrylates or ethylene acrylate copolymers; thermal stabilizers as described below with respect to polyamide composition C; and optional additives as described below with respect to polyamide composition C.

[0073] When solvent or one or more additional components are present in tie layer B, they are preferably present in 50 wt % or more, or 20 wt % or more, or 15 wt % or more, or 10 wt % or more, based on the total weight of the composition. Complementarily, the amount of polymer B1 and aminosilane B2 in the composition is 50 wt % or less, or 80 wt % or less, or 85 wt % or less, or 90 wt % or less, based on the total weight of the composition. The sum of the wt % of all components in the composition is 100 wt %. Alternatively, when the optional component is also suitable for use in polymer composition C, it can be present in the same amount suitable for use in polyamide composition C.

[0074] Preparation of the tie layer (B)

[0075] Forming a connection layer (B) on metal (A)

[0076] Referring now to the drawings, wherein like reference numerals designate corresponding structure throughout the several views, and in particular to Figure 3, these compositions can be applied to the metal (A) 11 by any known method such as spraying, roller coating or dipping, and then the solvent (if present) is evaporated (i.e., removed) to form the connecting layer (B) 21 on the metal (A) 11. The evaporation of the solvent can be carried out under any suitable known conditions, such as at room temperature or under heating, and under atmospheric pressure or under reduced pressure. Without being bound by theory, it is believed that when the composition is applied to the metal (A) 11, the hydroxyl groups of the amino-silane interact with the hydroxyl groups on the metal surface, and then when the solvent is removed, the amino-silane will be bonded to the surface of the metal (A) 11 by dehydration, such as Figure 3 shown.

[0077] Reference now Figure 2 , the connecting layer (B) 21 can be optionally heated after it is applied to the metal (A) 11, for example at 100 to 300 degrees Celsius for 1 to 120 minutes. Without being bound by theory, it is believed that when the connecting layer (B) 21 is heated, two adjacent carboxylic acid groups of the polymer (B1) chemically react with the primary amine groups of the amino-silane (B2) to form cyclic imide groups, which covalently bond the amino-silane molecules to the polymer molecules. Therefore, if the heating step is added, the connecting layer (B) 21 is considered to be the reaction product of the polymer (B1) and the amino-silane (B2), such as Figure 2 However, this step may be omitted because the tie layer (B) 21 is heated during the lamination step of the polyamide (C) as disclosed later.

[0078] The molar ratio of two adjacent carboxylic acid groups in polymer (B1) to the primary amine groups in amino-silane (B2) (acid:amine) is from 1:0.8 to 1:12, preferably from 1:0.9 to 1:6, more preferably from 1:0.9 to 1:5, further more preferably from 1:1 to 1:4, and still more preferably from 1:1.3 to 1:4. The molar ratios described herein are based on the fact that one anhydride group provides two carboxylic acid groups upon hydrolysis.

[0079] After forming the layer (B) 21 on the metal (A) 11, the metal can be used as a stable metal part. The metal part with the connecting layer (B) can be stored, distributed and used as a component ready for lamination with polyamide (C).

[0080] Polyamide composition (C)

[0081] The polyamide composition (C) can be in any shape, such as a sheet or plate, a tube or hose, or a box. When the polyamide composition (C) is a tube or hose, the end of the tube or hose can be placed in contact with the tie layer (B) on the metal (A). In other words, the polyamide metal laminate is not limited to a sheet or plate structure, and can be, for example, a polyamide hose bonded to a tie layer / metal part. Any article having a metal (A) bonded to the polyamide composition (C) by a tie layer (B) is within the scope of the present invention, regardless of the shape of the metal (A), the tie layer (B) or the polyamide composition (C), as long as some parts of the article have a structure metal (A) / tie layer (B) / polyamide composition (C), wherein (A), (B) and (C) are continuous layers. More preferably, the metal (A) is in direct contact with the tie layer (B), the tie layer (B) is in direct contact with the polyamide composition (C), and the metal (A) and the polyamide composition (C) are in direct contact with the opposite side of the tie layer (B).

[0082] Polyamide resin (C1)

[0083] The polyamide resin (C1) that can be used to prepare the polyamide metal laminate described herein is not limited, and can preferably be any polyamide having a melting point above about 170° C., preferably above about 180° C. The polyamide is a condensation product of one or more dicarboxylic acids and one or more diamines, and / or one or more aminocarboxylic acids, and / or a ring-opening polymerization product of one or more cyclic lactams. Suitable cyclic lactams are caprolactam and laurolactam. The polyamide can be fully aliphatic or semiaromatic.

[0084] Examples of polyamides that can be used in polyamide-metal laminates include poly(tetramethylene adipamide) (PA46), poly(ε-caprolactam) (PA 6), poly(hexamethylene adipamide / (ε-caprolactam / ) (PA 66 / 6), poly(hexamethylene adipamide) (PA 66), poly(hexamethylene adipamide / hexamethylene sebacamide) (PA66 / 610), poly(hexamethylene adipamide / hexamethylene dodecanedioamide) (PA66 / 612), poly(hexamethylene adipamide / decamethylene sebacamide) (PA66 / 1010), poly(hexamethylene sebacamide) (PA610), poly(hexamethylene dodecanedioamide) (PA612), poly(hexamethylene tetradecanediamide) (PA614), poly(tetramethylene adipamide / 2-methylpentamethylene adipamide) (PA46 / D6), poly(tetramethylene adipamide / tetramethylene terephthalamide) (PA46 / 4 T), poly (tetramethylene adipamide / hexamethylene terephthalamide) (PA46 / 6T), poly (tetramethylene adipamide / 2-methylpentamethylene adipamide / decamethylene terephthalamide) (PA46 / D6 / 10T), poly (hexamethylene adipamide / hexamethylene terephthalamide) (PA66 / 6T), poly (hexamethylene hexamethylene diamine / hexamethylene isophthalamide / hexamethylene terephthalamide PA66 / 6I / 6T, poly (hexamethylene adipamide / 2-methylpentamethylene adipamide) / hexamethylene terephthalamide (PA66 / D6 / 6T), poly (tetramethylene terephthalamide / hexamethylene hexamethylene diamine / hexamethylene isophthalamide / hexamethylene terephthalamide diamide) (PA4T / 66), poly (tetramethylene terephthalamide / ε-caprolactam) (PA4T / 6), poly (tetramethylene terephthalamide / hexamethylene dodecanedioamide) (PA4T / 612), poly (tetramethylene terephthalamide / 2-methylpentamethylene adipamide / hexamethylene adipamide) (PA4T / D6 / 66), poly (hexamethylene terephthalamide / 2-methylpentamethylene terephthalamide / hexamethylene adipamide) (PA6T / DT / 66), poly (hexamethylene terephthalamide / hexamethylene adipamide) PA6T / 66, poly (hexamethylene terephthalamide / hexamethylene dodecanedioamide) diamide) (PA6T / 610), poly (hexamethylene terephthalamide / hexamethylene dodecanediamide) (PA6T / 612), poly (hexamethylene terephthalamide / hexamethylene tetradecane diamide) (PA6T / 614), poly (hexamethylene terephthalamide / isophorone diamine terephthalamide) (PA6T / IPDT), poly (nonamethylene terephthalamide / nonamethylene sebacamide) (PA9T / 910), poly (nonamethylene terephthalamide / nonamethylene dodecanediamide) (PA9T / 912), poly (nonamethylene terephthalamide / 11-aminoundecaneamide) (PA9T / 11),Poly(nonamethylene terephthalamide / 12-aminododecanoamide) (PA9T / 12), poly(decamethylene terephthalamide / 11-aminoundecanoamide) (PA10T / 11), poly(decamethylene terephthalamide / 12-aminododecanoamide) (PA10T / 12), poly(decamethylene terephthalamide / decamethylene sebacamide) (PA10T / 1010), poly(decamethylene terephthalamide / decamethylene dodecanoamide) (PA10T / 1012), poly(decamethylene terephthalamide / Tetramethylene adipamide) (PA10T / 46), poly (decamethylene terephthalamide / ε-caprolactam) (PA10T / 6), poly (decamethylene terephthalamide / hexamethylene adipamide) (PA10T / 66), poly (dodecamethylene terephthalamide / dodecamethylene dodecane diamide) (PA12T / 1212), poly (dodecamethylene terephthalamide / ε-caprolactam) (PA12T / 6) and poly (dodecamethylene terephthalamide / hexamethylene adipamide) (PA12T / 66).

[0085] Preferred polyamides disclosed herein include PA6T / DT, PA66, PA612, PA610, PA6T / 610, PA6T / 612, PA6T / IPDT, PA6, PA10 and blends of these.

[0086] The amount of polyamide (C1) in the polyamide composition (C) is complementary to the amounts of the other components in the polyamide composition (C). In other words, the sum of the weight percentages of all components in the polyamide composition (C) is 100 weight percent. Thus, for example, if the polyamide composition (C) comprises 70 weight percent of reinforcing agent and 5 weight percent of thermal stabilizer, the amount of polyamide (C1) is 25 weight percent, based on the total weight of the polyamide composition (C).

[0087] Enhancer (C2)

[0088] The polyamide composition (C) described herein may include one or more reinforcing agents (C2). The reinforcing agent is preferably selected from the group consisting of calcium carbonate, glass fibers with circular and non-circular cross sections, glass flakes, glass beads, carbon fibers, aramid fibers, talc, mica, wollastonite, calcined clay, kaolin, diatomaceous earth, magnesium sulfate, magnesium silicate, barium sulfate, titanium dioxide, sodium aluminum carbonate, barium ferrite, potassium titanate, and a mixture of two or more suitable reinforcing agents (C2). In a preferred embodiment, the reinforcing agent is selected from the group consisting of glass fibers with circular cross sections, glass fibers with non-circular cross sections, and aramid fibers. The reinforcing agent may have a sizing agent or a coupling agent, an organic material, or an inorganic material, which may improve the bonding between the reinforcing agent and the polyamide resin.

[0089] The polyamide composition (C) described herein may comprise from 0 to 70 wt%, preferably 10 to 70 wt%, and most preferably 20 to 70 wt% of one or more reinforcing agents, based on the total weight percentage of all ingredients in the polyamide composition (C).

[0090] Heat stabilizer (C3)

[0091] The polyamide composition (C) may contain a heat stabilizer (C3). Organic heat stabilizers are preferred, since generally inorganic heat stabilizers provide halogen ions and / or copper ions, which affect the corrosion of the metal (A).

[0092] Organic heat stabilizers, also known as antioxidants, as disclosed herein include hindered phenol compounds, amine-based heat stabilizers, and phosphorus-based heat stabilizers.

[0093] Examples of hindered phenol compounds include Irganox TM 1010 Tetrakis(methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate))methane commercially available from CIBA Specialty Chemicals, Tarrytown, NY and also available from Irganox TM N,N'-hexamethylenebis(3,5-di-tert-butyl-hydroxyhydrocinnamic acid amide) is commercially available from Ciba Specialty Chemicals 1098. Other suitable hindered phenols include 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 1,6-hexamethylenebis(3,5-di-tert-butyl 4-hydroxyhydrocinnamate), both of which are available as Irganox TM 1330 and 259 were obtained from Ciba Specialty Chemicals.

[0094] Examples of amine-based heat stabilizers include hindered amine light stabilizers (HALS). Preferably, the HALS is a compound derived from a substituted piperidine compound, in particular any compound derived from an alkyl-substituted piperidinyl, piperidinyl or piperazinone compound and a substituted alkoxypiperidinyl compound. Examples of such compounds are: 2,2,6,6-tetramethyl-4-piperidone; 2,2,6,6-tetramethyl-4-piperidinol; bis-(1,2,2,6,6-pentamethylpiperidinyl)-(3',5'-di-tert-butyl-4'-hydroxybenzyl)butylmalonate; bis-(2,2,6,6-tetramethyl-4-piperidinyl) sebacate ( 770, MW 481); oligomers of N-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-piperidinol and succinic acid ( 622); Cyanuric acid and N,N-bis(2,2,6,6-tetramethyl-4-piperidinyl)-hexamethylenediamine oligomers; Bis-(2,2,6,6-tetramethyl-4-piperidinyl) succinate; Bis-(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate ( 123); Bis-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate ( 765); 144; XT850; Tetrakis-(2,2,6,6-tetramethyl-4-piperidinyl)-1,2,3,4-butanetetracarboxylate; N,N'-bis-(2,2,6,6-tetramethyl-4-piperidinyl)-hexane-1,6-diamine ( T5); N-butyl-2,2,6,6-tetramethyl-4-piperidinamine; 2,2'-[(2,2,6,6-tetramethyl-piperidinyl)-imino]-bis-[ethanol]; poly((6-morpholine-S-triazine-2,4-diyl)(2,2,6,6-tetramethyl-4-piperidinyl)-iminohexamethylene-(2,2,6,6-tetramethyl-4-piperidinyl)-imino)( UV 3346); 5-(2,2,6,6-tetramethyl-4-piperidinyl)-2-cyclo-undecyl-oxazole)( N20); 1,1'-(1,2-ethane-diyl)-bis-(3,3',5,5'-tetramethyl-piperazinone); 8-acetyl-3-dodecyl-7,7,9,9-tetramethyl-1,3,8-triazaspiro(4,5)decane-2,4-dione; polymethylpropyl-3-oxy-[4(2,2,6,6-tetramethyl)-piperidinyl]siloxane( 299); 1,2,3,4-butane-tetracarboxylic acid-1,2,3-tris(1,2,2,6,6-pentamethyl-4-piperidinyl)-4-tridecyl ester; copolymer of α-methylstyrene-N-(2,2,6,6-tetramethyl-4-piperidinyl)maleimide and N-stearylmaleimide; polymer of 1,2,3,4-butanetetracarboxylic acid with β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol and 1,2,2,6,6-pentamethyl-4-piperidinyl ester ( LA63); β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol polymer with 1,2,3,4-butanetetracarboxylic acid and 2,2,6,6-tetramethyl-4-piperidinyl ester ( LA68); 1,3:2,4-bis-O-(2,2,6,6-tetramethyl-4-piperidinylidene)-D-glucitol (HALS 7); oligomers of 2,2,4,4-tetramethyl-20-(oxiranylmethyl)-7-oxa-3,20-diazabispiro[5.1.11.2]-heneicosane-21-one ( N30); [(4-methoxyphenyl)methylene]-malonic acid bis(1,2,2,6,6-pentamethyl-4-piperidinyl) ester ( PR 31); N,N'-1,6-hexanediylbis[N-(2,2,6,6-tetramethyl-4-piperidinylcarboxamide( 4050H); N,N"'-[1,2-ethanediylbis[[[4,6-bis[butyl(1,2,2,6,6-pentamethyl-4-piperidinyl)amino]-1,3,5-triazine-2-yl]imino]-3,1-propanediyl]]-bis[N',N"-dibutyl-N',N"-bis(1,2,2,6,6-pentamethyl-4-piperidinyl)1,3,5-triazine-2,4,6-triamine ( 119MW 2286); poly[[6-[(1,1,3,33-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)-imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]]( 944MW 2000-3000); 1,5-dioxaspiro(5,5)undecane 3,3-dicarboxylic acid bis(2,2,6,6-tetramethyl-4-piperidinyl) ester ( UV-500); 1,5-dioxaspiro(5,5)undecane 3,3-dicarboxylic acid bis(1,2,2,6,6-pentamethyl-4-piperidinyl) ester ( UV-516); N-2,2,6,6-tetramethyl-4-piperidinyl-N-amino-oxalamide; 4-acryloyloxy-1,2,2,6,6-pentamethyl-4-piperidine; 1,5,8,12-tetrakis[2',4'-bis(1",2",2",6",6"-pentamethyl-4"-piperidinyl(butyl)amino)-1',3',5'-triazine-6'-yl]-1,5,8,12-tetraazadodecane; HALS PB-41 (Clariant Huningue SA); S-EED (Clariant Huenanger GmbH); 3-Dodecyl-1-(2,2,6,6-tetramethyl-4-piperidinyl)-pyrrolidine-2,5-dione; HA88; 1,1'-(1,2-ethane-diyl)-bis-(3,3',5,5'-tetramethyl-piperazinone) ( 3034); 1,1'1"-(1,3,5-triazine-2,4,6-triyltris((cyclohexylimino)-2,1-ethanediyl)tris(3,3,5,5-tetramethylpiperazinone)( 3150); and 1,1',1"-(1,3,5-triazine-2,4,6-triyltris((cyclohexylimino)-2,1-ethanediyl)tris(3,3,4,5,5-tetramethylpiperazinone) ( 3159). ( and Materials available from Ciba Specialty Chemicals; Materials available from Cytec Technology Corp. Materials available from Great Lakes Chemical Corp.; and Materials available from Clariant Corp.; Materials available from BASF; The materials are available from participating industrial companies (Partecipazioni Industriali); and Materials available from BFGoodrich Co.; Materials available from Asahi Denka Co.

[0095] Other specific HALS are selected from the group consisting of: di-(2,2,6,6-tetramethyl-4-piperidinyl) sebacate ( 770,MW 481) S-EED (Clariant Hunenger GmbH); N,N"'-[1,2-ethanediylbis[[[4,6-bis[butyl(1,2,2,6,6-pentamethyl-4-piperidinyl)amino]-1,3,5-triazine-2-yl]imino]-3,1-propanediyl]]-bis[N',N"-dibutyl-N',N"-bis(1,2,2,6,6-pentamethyl-4-piperidinyl)1,3,5-triazine-2,4,6-triamine ( 119MW 2286); and poly[[6-[(1,1,3,33-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)-imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]]( 944MW2000-3000).

[0096] The concentration of the optional heat stabilizer (when present) in the polyamide composition (C) is in the range of from about 0.01 to 5 wt. %, preferably from 0.1 to 4 wt. %, and more preferably from 0.1 to 2 wt. %, based on the total weight of all ingredients in the polyamide composition (C).

[0097] additive

[0098] Optional additives that can be added to the polyamide composition (C) include, for example, waxes, UV stabilizers, colorants, lubricants, and mixtures of these. Optional additives can also include materials that, when added to the polyamide composition (C) described herein, produce a polyamide composition (C) having a linear thermal expansion coefficient similar to that of the metal used. For aluminum, an example of such an additive is aramid fiber, such as DuPont TM Aramid fiber.

[0099] The concentration of additives (when present) in the polyamide composition (C) ranges from about 0.01 to 25 wt%, preferably 0.1 to 20 wt%, based on the total weight of all ingredients in the polyamide composition (C).

[0100] Preparation of polyamide metal laminates

[0101] The polyamide-metal laminate described herein can generally be prepared by the following steps:

[0102] a) forming a tie layer on the metal to provide a metal / tie layer laminate;

[0103] b) bonding said metal / tie layer laminate from step a) to a polyamide composition to provide a polyamide metal laminate.

[0104] Step a) is the same as described above with respect to forming a tie layer (B) on metal (A). As mentioned, the heating step of the tie layer (B) is optional. Without being bound by theory, it is believed that when the tie layer (B) is heated, the carboxylic acid groups or carboxylic acid dibasic groups of the polymer (B1) react with the amino-silane (B2).

[0105] There are several practical methods for step (b). The first suitable method is to prepare the shaped polyamide in advance and then bond it to the surface of the connecting layer prepared in step (a). This method is also called welding (method). Specifically, the polyamide metal laminate can be prepared by the following procedure.

[0106] The polyamide composition (C) can be shaped using any procedure, such as molding, extrusion or compression, to make the polyamide composition (C) into a desired shape, such as a tube or hose. The shaped polyamide composition (C) is contacted with a metal-connecting layer laminate as disclosed herein. The polyamide composition (C) and the metal-connecting layer laminate are heated when in contact with each other, preferably under pressure, to a temperature of 200° C. to 350° C., for a period of time sufficient to melt the polyamide resin (C1) and allow the polyamide amine group to react with the acid group of the connecting layer (B). Any welding method can be used, for example, using a heating device such as an oven or hot plate, laser welding, ultrasonic welding and hot air welding. Exemplary hot pressing conditions are 220 to 320 degrees Celsius for 1 to 120 seconds at 0.1 MPa or higher. If used, the pressure is released to obtain an article comprising a polyamide-metal laminate.

[0107] A second suitable method is to feed a polyamide composition comprising polyamide (C1) and optionally reinforcing agent (C2) and heat stabilizer (C3) into an injection molding device, melt mix to form polyamide composition (C), and then mold the polyamide composition (C) directly on the surface of the metal-connecting layer laminate, preferably by injection molding. Without wishing to be bound by theory, it is assumed that polyamide (C1) melts during the injection of polyamide composition (C). Therefore, it is further assumed that the temperature of the connecting metal laminate and the injected polyamide composition (C) is high enough to react the amine groups of polyamide (C1) with the acid groups of the connecting layer (B).

[0108] When a tie layer (B) is used to bond the polyamide composition (C) to the metal (A), the resulting polyamide-metal laminate exhibits a combination of desirable bond strength between the polyamide composition (C) and the metal (A) and excellent hydrolysis resistance. Without being bound by theory, it is believed that the amine terminal groups of the polyamide bond with the carboxylic acid groups of the polymer to provide imide groups that connect or chemically bond the polyamide molecules to the tie layer.

[0109] Polyamide-metal laminates

[0110] The obtained polyamide-metal laminate bonded by the specific tie layer exhibits desirable bonding strength and excellent hydrolysis resistance, which is greater than that of the laminate using the conventional surface treatment agent (aminopropylsilane). In particular, the polyamide-metal laminate using the tie layer of the present invention exhibits desirable hydrolysis resistance when exposed to an ethylene glycol / water solution at 130° C. for 1000 hours, compared to the initial bonding strength before exposure to the ethylene glycol / water solution. Figure 1 , depicting the expected structure of the polyamide-metal laminate of the present invention. Without wishing to be bound by theory, it is believed that the silanol groups of the tie layer 21 react with the hydroxyl groups of the metal (e.g., aluminum) 11, and the two carboxylic acid groups of the tie layer 21 form a cyclic imide structure with the nitrogen atom of the amino group of the polyamide composition 31. Therefore, the aluminum 11 and the polyamide composition 31 are firmly bonded via the tie layer 21. On the other hand, as Figure 5 As shown, when using conventional surface treatment agents such as aminopropylsilane, the interaction between the carboxylic acid groups of the polyamide composition 31 and the amino groups of the amino-silane is very weak, especially in the presence of water (hydrolysis). Figure 4 Another comparative model is shown when amino-silane is not included in the tie layer. Although the polyamide composition 31 can bond with the polymer 23, the interaction between the carboxylic acid of the polymer 23 and the hydroxyl group of the aluminum 11 is weak, so the desired bonding strength between the aluminum 11 and the polyamide composition 31 can be obtained.

[0111] Products

[0112] The articles of the invention comprise the polyamide-metal laminates disclosed above. These articles can be used in any technology requiring direct adhesion of metal to polyamide. Examples of such technologies include the automotive, electronics and construction industries. In particular, these articles can be used for pipes, hoses, water pump housings, oil filter housings and transmission housings in automotive technology.

[0113] The following examples are provided to further describe the present invention in detail. These examples, which set forth preferred modes presently considered for carrying out the invention, are intended to illustrate but not to limit the invention.

[0114] Examples

[0115] The products which are examples of the present invention are indicated by "E" in the following table, while the comparative examples are indicated by "C" in the following table.

[0116] Material

[0117] In the compositions, methods and articles exemplified in the following tables, the following materials were used. Unless otherwise indicated, all percentages are by weight.

[0118] Metal layer (A)

[0119] Metal 1: Aluminum, containing 1.2 to 0.8 weight percent magnesium, 0.7 weight percent iron, 0.4 to 0.8 weight percent silicon dioxide, and up to 1.4 weight percent other metals, and available as A6061 of JIS (Japanese Industrial Standard).

[0120] Metal 2: Aluminum, containing 2.2 to 2.8 weight percent of magnesium and up to 1.3 weight percent of other metals, and available as A5052 of JIS.

[0121] Metal 3: Aluminum, containing more than 99.5 weight percent aluminum and at most 0.5 weight percent other metals, and available as A1050 of JIS.

[0122] Polymer (B1)

[0123] Polymer A: Ethylene maleic anhydride copolymer, available as ZeMac E60 from Vertellus Specialties Inc., reportedly a 1:1 alternating copolymer of ethylene and maleic anhydride.

[0124] Polymer B: Polybutadiene-maleic acid copolymer, available from Polysciences, Inc. as poly(butadiene-maleic acid) at 42% solids in water.

[0125] Aminosilane (B2)

[0126] Silane A: A 30 weight percent aqueous solution of the hydrolyzate of 3-aminopropyltrimethoxysilane and available as KBP-90 from ShinEtsu Silicone.

[0127] Silane B: an amino-silane coupling agent comprising N-2-(aminoethyl)-3-aminopropyltrimethoxysilane and available as KBM-603 from Shin-Etsu Silicone Co., Ltd.

[0128] Silane C: an amino-silane coupling agent, comprising 3-aminopropyltriethoxysilane, and available as KBE-903 from Shin-Etsu Silicone Co., Ltd.

[0129] Silane D: A 30 weight percent aqueous solution of the hydrolyzed product N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, obtained as KBP-64 from Shin-Etsu Silicone Co., Ltd.

[0130] Polyamide composition (C)

[0131] Polyamide A (PA-A): a polyamide composition comprising 51% PA66, 13% PA6, 35 weight percent glass fiber and an organic heat stabilizer, wherein PA66 has a melting point of 260°C and PA6 has a melting point of 221°C.

[0132] Polyamide B (PA-B): a polyamide composition comprising 66% PA66, 33% glass fiber and no heat stabilizer, wherein PA66 has a melting point of 260°C.

[0133] Polyamide C (PA-C): a polyamide composition comprising 66% PA612, 33% glass fiber and an organic heat stabilizer, wherein PA612 has a melting point of 218°C.

[0134] Polyamide D (PA-D): a polyamide composition comprising 65% PA612, 33% glass fiber and no heat stabilizer, wherein PA612 has a melting point of 218°C.

[0135] Polyamide E (PA-E): a polyamide composition comprising 63% PA6T / DT, 35% glass fiber and an organic heat stabilizer, wherein the PA6T / DT has a melting point of 300°C.

[0136] Heat stabilizer (C3)

[0137] HS2-A: an organic heat stabilizer, comprising a mixture of Chimasorb 944FDL 0.3%, Irganox 1098 0.75%, and Ultranox 626A 0.3%, wherein these weights are based on the weight of the polyamide composition C.

[0138] HS2-B: Organic heat stabilizer, 1098 from BASF.

[0139] Prior to treating the aluminum with a metal treatment solution as disclosed herein, the aluminum surface may be cleaned by one of the following cleaning procedures:

[0140] Cleaning procedures

[0141] Procedure A—Expose the aluminum surface to isopropyl alcohol.

[0142] Procedure B - The aluminum surface was polished with an abrasive (500 grit sandpaper) to provide a polished aluminum surface, and then the aluminum surface was exposed to a cleaning solution, followed by rinsing the treated aluminum surface with a detergent solution to remove residual cleaning solution.

[0143] Procedure C - The aluminum surface was blasted with alumina particles (#240) at 0.2 MPa using Baby-blast manufactured by Macoho Co., Ltd.

[0144] Procedure D - 14 mW / cm at room temperature (26°C) 2 Irradiate with ultraviolet light (254nm) at a distance of 5cm for 1 hour.

[0145] Welding A (Hot Pressure Welding)

[0146] Reference now Figure 6 , the polyamide cap 41 has a cylindrical cross section in a horizontal plane perpendicular to the vertical plane through which the cross section of the polyamide cap 41 is depicted. This cylindrical portion is the welding area 42 through which the polyamide cap 41 will be connected to the metal layer A. Now refer to Figure 7 , an aluminum test plate 43 (50 mm square and 6 mm thick) has a circular hole (25 mm) in the center. The aluminum test plate 43 is cleaned and then treated with a metal treatment solution to produce a connecting layer 44 on the metal surface. The polyamide cap test sample 41 is placed in contact with the aluminum plate 43 and centered so that the polyamide cap 41 covers the circular hole. The surface area 42 of the polyamide cap 41 in contact with the aluminum plate 43 is approximately 177 mm 2 The aluminum plate 43 and the cap 41 are placed onto a hot plate 46, while a metal cylinder 45 is placed, which transmits pressure to just above the welding area 42. The direction of pressure is indicated by the arrow. This assembly is hot pressed at 0.3 MPa at 240 to 315 degrees Celsius for 1 minute, and then cooled to a temperature below the melting temperature of the polyamide composition (C) under the same pressure.

[0147] Welding B (direct injection molding)

[0148] Reference now Fig. 9 , an aluminum plate 50 having a width of 18 mm, a length of 45 mm and a thickness of 2.0 mm was used as an aluminum test plate. The aluminum plate 50 was cleaned and then treated with a metal treatment solution, which deposited a connecting layer B on the aluminum plate 50. The aluminum plate 50 was placed in a molding tool, and then a polyamide molding 51 having a width of 10 mm, a length of 45 mm and a thickness of 3 mm was formed on the aluminum plate 50 by direct molding with an overlap area 52 of 10×5 mm. The set cylinder temperature in the polyamide housing was 280° C. to 300° C., and the tool temperature was 120° C. to 160° C. The heating and cooling system “Y-HeaT” of Yamashita Electric Co., Ltd. was used for direct injection molding, with a heating temperature of 240° C. and a cooling temperature of 180° C., a holding pressure of 40 MPa, and a holding time of 6 seconds.

[0149] Bond Strength Retention Test

[0150] Two specimens were prepared for each polyamide composition and surface treatment solution. One specimen was exposed to an aqueous ethylene glycol solution heated at 130° C. for 1,000 hours (unless otherwise specified) to observe hydrolysis resistance, while the second specimen was not exposed to the solution. The bonding strength of the two specimens was measured.

[0151] The specimens were tested for bond strength of the molded polyamide composition to the aluminum plate after exposure to a heated aqueous glycol solution. Figure 8 For weld A, the cap-molded polyamide 41 is pushed from the inside of the cap by a piston 48 of 32 mm length and 8 mm shaft diameter. The arrow indicates the direction of the applied force. The metal plate 47 is held in place by a metal cylinder 49 until the polyamide cap 41 is completely separated from the plate 47. For weld B, the specimen is held in a sample holder based on ISO 19095-3, §5.2.1.2 Figure 1 The measurement was carried out at a crosshead speed of 10 mm / min until fracture. The shear stress (MPa) was calculated by dividing the fracture load (N) by the joint area (mm 2 ). The maximum force required to separate the molded polyamide composition from the aluminum plate is the bond strength of the specimen. The bond strength of the specimen not exposed to the aqueous ethylene glycol solution is compared with the bond strength of the specimen prepared by the same method but exposed to the aqueous ethylene glycol solution. The difference between the bond strength of the specimen after exposure to the aqueous ethylene glycol solution and the bond strength of the specimen not exposed to the aqueous ethylene glycol solution represents the bond strength retention of the specimen.

[0152] Table 1 shows the composition of the polyamide layer used in the examples and comparative examples. Table 2 shows the composition of the solvent solution used to apply the tie layer (B) to the aluminum before bonding the aluminum to the polyamide layer. In Tables 1 and 2, the values ​​are weight percentages based on the total weight of the polyamide composition in Table 1 and based on the total weight of the metal treatment solution in Table 2. Tables 3 and 4 show the bond strength retention values ​​of various samples.

[0153] Table 1

[0154]

[0155]

[0156] Table 2

[0157]

[0158] Table 3

[0159]

[0160]

[0161] Table 3 shows that the tie layer improves the hydrolysis resistance between the molded polyamide composition and aluminum. See also the results obtained for Comparative Example C10 below. When aliphatic polyamides are used, the desired bond strength retention is obtained. PA 66 or a blend of PA 66 and PA 6 is used in E1 and E2, respectively. PA 612 is used in E3 and E4. E5 uses a semi-aromatic polyamide PA 6T / DT, and articles made from this polyamide using the tie layer disclosed herein also show the desired bond strength retention characteristics.

[0162] Table 3 also shows the effect of various heat stabilizers on the retention of the bond strength between the polyamide composition and aluminum. These examples (E1 to E7) show that the resulting bond strength between the molded polyamide composition and aluminum is retained at least 7.1 percent after the article is exposed to an ethylene glycol / water solution at 130°C for 1000 hours.

[0163] Table 4

[0164]

[0165]

[0166] Table 4 shows the effect of the ratio of amino-silane material to polymer in the metal treatment solution on bond strength retention. In C8, the ratio of amino-silane material to polymer was about 1 to 14.4, which was outside the desired range of 1 to 0.8 to 1 to 12, resulting in a bond strength retention of less than 1 percent.

[0167] Table 4 also shows how solvent solutions containing various amino-silane materials and polymers affect the effectiveness of such metal treatment solutions in maintaining the bond strength of the molded polyamide composition to aluminum. The solvent solution of E11 contains a polybutadiene-maleic acid copolymer. This solvent solution provides the desired bond strength maintenance between the aluminum and the molded polyamide composition, indicating that both acid- and anhydride-based copolymers can be used to prepare the solvent solutions described herein.

[0168] The solvent solution used in C10 does not contain a polymer. The solvent solution used in C11 does not contain an amino-silane material. In both comparative examples, the desired bond strength retention was not obtained. C12 contains N-2-(aminoethyl)-3-aminopropyltrimethoxysilane as an amino-silane material and the resulting article does not show the desired bond strength retention.

[0169] C9 shows the effect of the ratio of amino-silane material to polymer in the metal treatment solution on bond strength retention. In C9, the ratio of amino-silane material to polymer was about 5.8 to 1, which was outside the desired range of 3 to 1 to 0.8 to 8, resulting in a bond strength retention of less than one percent.

[0170] Table 5

[0171]

[0172]

[0173] Table 5 shows the effects of different cleaning methods and welding methods (direct injection molding). Reference Example 13, Example 14 and Comparative Example 13, cleaning procedure A did not achieve good bonding strength. Reference Example 15, the polyamide-metal laminate formed by direct injection molding (welding B) exhibited the same excellent hydrolysis resistance as the sample formed by hot compression molding (welding A).

[0174] Surface analysis of aluminum plate

[0175] The surface of the aluminum plate was analyzed by XPS or TOF-SIMS after the cleaning process was performed. Procedure B or D disclosed above was selected. The plate of Comparative Example 14 (C14) was wiped with a cloth soaked in oil after cleaning the surface by procedure B. After the surface analysis, polyamide was laminated in the same manner as in Example 1. Bond strength and hydrolysis resistance were analyzed.

[0176] XPS measurement QuanteraSXM from PHI Co., Ltd. (PHI co., inc.), X-ray source: Al (1486.6eV), detection area: Micrometer, detection depth 4-5nm, measurement mode: wide scan: Al2p, O1s, C1s, the signal percentage of each element is determined by peak area curve fitting.

[0177] TOF-SIMS: Machine: TOF.SIMS5-300 from IONTOF GmbH, Test conditions: Main ion: Bi, Analysis area: 300 μm. Mass analyzer: Time-of-flight mass spectrometer, by reacting with Al, Al(OH)3, Al2O3 or AlO(OH) n Each mass fragment was determined by comparison with the H2O standard sample data.

[0178] Table 6

[0179]

[0180]

[0181] Table 6 shows the effect of aluminum surface condition. Referring to E16 and C14, oil contamination reduces bond strength even after the same surface cleaning B. Referring to C15 and E18, surface cleaning (such as polishing and UV / ozone treatment) is necessary for good bond strength, and the effectiveness of these can be verified by TOF-SIMS with Al(OH)3 or partial aluminum hydroxide compounds (such as AlO(OH) n H2O) fragments to detect.

[0182] Table 7

[0183]

[0184]

[0185] Table 8

[0186]

[0187] To further elucidate the molar ratio of amino-silane material to polymer, the bond strength retention of articles made from molded polyamide (PA66) and aluminum by hot pressure welding (Weld B) after exposure to ethylene glycol / water solutions at 130°C for 250 hours has been measured in several solvent solutions.

[0188] Table 7 shows solvent solutions containing different ratios of amino-silane materials and ethylene maleic acid copolymers.

[0189] In E18 to E27, the ratio of amino-silane material to polymer was about 1 to 19, resulting in a desired initial bond strength in excess of 50 MPa.

[0190] Furthermore, in E19 to E24, the molar ratio of amino-silane to polymer was about 1:1.3 to 1:4, and excellent bond strength retention of at least 20 MPa was exhibited after the article was exposed to an ethylene glycol / water solution at 130° C. for 250 hours.

[0191] Table 9

[0192]

[0193] Table 9 shows the weld strength after exposure to 90°C water for 96 hours. E28 using SS-21 containing polymer D, a hydrolyzate of diamine-type amino-silane, and polymer A exhibited excellent bond strength, while C17 using SS-8 consisting of only amino-silane exhibited 0 MPa after exposure. It can be seen that diamine-type amino-silanes having terminal -NH2 groups can also effectively obtain good hydrolysis resistance when hydrolyzed.

[0194] Although certain preferred embodiments of the present invention have been described and specifically illustrated above, the present invention is not intended to be limited to such embodiments. Rather, it should be understood that although many features and advantages of the present invention have been set forth in the foregoing description, together with details of the structure and function of the present invention, the present disclosure is illustrative only, and changes may be made in detail, especially in shape, size and arrangement of parts, within the principle of the present invention to the full extent indicated by the broad general meaning of the terms expressing the appended claims.

Claims

1. A composition suitable for laminating polyamide onto a metal surface, the composition comprising: (B1) a polymer comprising carboxylic acid groups, (B2) an amino-silane comprising a primary amine group and at least one hydroxyl group, and (B3)Water, wherein at least two carboxylic acid groups in polymer (B1) are adjacent to each other, and the molar ratio of the carboxylic acid groups in (B1) to the primary amine groups in (B2) is from 0.8:1 to 12:1, and wherein water is present in an amount of 10 wt.% or more based on the total weight of the composition.

2. The composition according to claim 1, wherein The pH of the composition is 5 or higher.

3. The composition according to claim 1, wherein The content of the two adjacent carboxylic acid groups in the polymer (B1) is 2 wt% or more based on the total wt% of the polymer (B1).

4. The composition according to claim 1, wherein The polymer (B1) comprises one or more polymers selected from the group consisting of poly(butadiene-maleic acid) copolymers, propylene-maleic acid copolymers, ethylene-maleic acid copolymers, ethylene-maleic anhydride copolymers, propylene-maleic anhydride copolymers, polymaleic acid, maleic anhydride-grafted ethylene octene copolymers, maleic anhydride-grafted ethylene butene copolymers and maleic anhydride-grafted ethylene propylene copolymers.

5. The composition according to claim 1, wherein Amino-silane (B2) is represented by formula (I): wherein R1, R2 and R3 are independently selected from H, C1 to C6 linear, branched or cyclic alkyl; R4 is H; R5 is independently selected from H and -(CH2)y-NH2; x and y are independently in the range from 1 to 6; and at least one of R1, R2 and R3 is H. 6 . A metal part having a connecting layer on a surface of the metal part, wherein the connecting layer is the composition of claim 1 .

7. A method for laminating polyamide on a surface of aluminum, the method comprising the steps of: (i) preparing aluminum, wherein the surface of the aluminum is cleaned, (ii) applying the composition as claimed in claim 1 to form a connecting layer on the surface of the aluminum, and then (iii) laminating a polyamide composition onto the tie layer under heating at least to a temperature at which the polyamide melts.

8. A polyamide-metal laminate formed by the method of claim 7, comprising (A) a metal, (B) a tie layer formed on a surface of the metal, and (C) a polyamide composition formed on a surface of the tie layer, wherein the tie layer comprises: (B1) a polymer comprising carboxylic acid groups; and (B2) an amino-silane comprising a primary amine group and at least one hydroxyl group; Wherein at least two carboxylic acid groups in the polymer (B1) are adjacent to each other, and the molar ratio of the carboxylic acid groups in the polymer (B1) to the primary amine groups in the amino-silane (B2) is from 0.8:1 to 12:

1.

9. The polyamide-metal laminate according to claim 8, wherein The metal (A) is aluminum.

10. The polyamide-metal laminate according to claim 9, wherein The aluminum has a hydroxyl group on a surface of the aluminum.

11. An article comprising the polyamide-metal laminate of claim 8.

12. The article of claim 11 selected from the group consisting of a pipe, a hose, a water pump housing, an oil filter housing, and a transmission housing.